Death by Ram Attack: A Case Report from Greece and a Brief Review of the Literature. Issue 5 (9th July 2019) - Katsos, Konstantinos D.; Sakelliadis, Emmanouil I.; Moraitis, Konstantinos; Spiliopoulou, Chara A.
Abstract: A case of a ram attack that caused injuries to a 73‐year‐old man is presented. The deceased survived the attack and had the opportunity to speak with a friend over the phone before being transferred to the hospital. After a 21‐day hospitalization, the patient passed away. A postmortem examination was performed to ascertain the cause of death. The autopsy findings are presented along with a brief review of the literature. Attacks by agricultural animals (or livestock) around the world are reported in the scientific literature. Fatalities from ram attacks are extremely rare. The need to implement specific codes in the ICD system, relevant to each animal attack, appears to be of great importance, in order to allow tracking of animal‐related deaths.